Matrizes das protolinguagens - Silva, Júlio Cesar Martins da (2010)
This research presents an initial proposition which aims to expand externally the work presented in Matrix of languages: sonorous, visual and verbal. Applications on hipermídia (originally in portuguese: Matrizes da linguagem e pensamento: sonora, visual, verbal. Aplicações na Hipermídia. São Paulo Iluminuras/FAPESP, 2001) by Lucia Santaella, creating two new matrices (1 Quality and 2 Relation) aiming to reach a composition of three matrices, founded in Peirce s philosophical architecture, the same way thrilled by Santaella s work. According to original proposition all kinds of languages are hybrid and rise from mixtures, in different grades, of these three main matrixes of languages, which expands itself internally, in a recursive way, according phenomenological three categories from Peirce, reaching 27 modalities, which are expanded internally again, each one, until reach 81 modalities. The proposition of this research, described initially as external expansion, consists in to create two new matrixes to operate in conjunction with the matrixes of language, but containing less refinement. The research justify itself by the necessity of understand all kinds of languages engendered by human being as a gender throughout your relation with physical world and posterior representation from him, starting from a unique and entangled conceptual structure, able to vary in grades from most primordial elements from physical world to one most structured verbal language, passing through human sensorial perception. The research has the main objective of to propose and an initial and provisory structure of these new matrixes of protolanguages, taken here as the primordial types, without grammar among other characteristics. The group of three matrixes is so called Matrix 1 Quality: nature phenomena; Matrix 2 Relation: sensorial perception; Matrix 3 Representation: Languages. This last one corresponds exactly to original proposition of Santaella s work. Founded in Peirce s three phenomenological categories, theory of signs and semiosis, this research starts from assumption that if the matrixes of languages correspond to thirdness category, certainly should have two other matrixes which corresponds to secondness and firtness. From that emerges the hypothesis that these matrixes should have some relationship with phenomena from physical world (firstness) and the human sensorial perception (secondness), which captures those phenomena, bringing to our mental processes. This way, the matrix 1 was proposed corresponding to phenomena based on Newton s 2nd laws of classical Physics which puts in relation force, mass and acceleration as initial inspiration; the matrix 2 was proposed based on physiological senses of smell, taste and touch, where the sense of smell corresponds to most primordial and the sense of touch the less primordial one. The auditory and visual senses are already included in Santaella s work. Each one of these two matrixes is presented in a provisory and initial structured where each one of them have three main divisions, which are expanded three by three according Peirce s three categories, reaching 9 modalities, which are subdivided again, each one of them, until 27 modalities. Although the refining grades (in quantity of sublevels) are less unfolded than those reached by Santaella s work, this was result from strategic decision in order to obtain the initial structure of two new matrixes. The initial results are very interesting and justify by itself the necessity of research towards to continuous refining work. The three matrixes resulted from creation of two matrixes of protolanguages in addition to matrixes of language proposed by Santaella, presents an remarkable correspondence with the ten classes of signs from Peirce. If the three matrixes of languages already increase our potential to understand better the existing languages and the new ones which will certainly appear, the trio of matrixes, could be an significant improvement to this potential